Morphometrics of the larval stages of Lernaea polymorpha yu and L. Cyprinacea linnaeus (copepoda) - Shariff, M.; Sommerville, C. (Brill Academic Publishers, 1989)
Morphometric studies were carried out on the larval stages of Lernaea polymorpha and L. cyprinacea in order to determine whether they could be a reliable method for species identification. The studies concentrated on 8 characteristics of developmental stages in L. polymorpha on Aristichthys nobilis, and in L. cyprinacea on A. nobilis and Carassius auratus. The results showed morphometric variations of the different larval stages in L. cyprinacea obtained on different hosts, while similarities were observed between the larval stages of L. cyprinacea and L. polymorpha reared under the same conditions. Certain characteristics were not affected by the host species in either Lernaea. These included the length of the genital segment in the 5th female cyclopoid stage and the length of antennulae in the cyclopoid stages in both sexes. The results were compared with those obtained in other studies.